KEBIJAKAN HUKUM TERHADAP INDIVIDU TANPA KEWARGANEGARAAN BERDASARKAN PERSPEKTIF HAK ASASI MANUSIA DAN KONSTITUSI - Istikhomah (Refleksi Hukum: Jurnal Ilmu Hukum, 2025)
This article examines Indonesia’s legal policies toward stateless individuals from the perspectives of human rights and constitutional law. The main issue addressed is whether Indonesia’s Citizenship Law aligns with human rights principles in providing adequate protection for this vulnerable group. Stateless individuals often lose access to fundamental rights, including education, healthcare, and employment. Through an analysis of international legal instruments, the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945), which guarantees every person’s right to citizenship and related national legislation, this study identifies a gap between the normative legal framework and its practical implementation. Although the Constitution formally safeguards the right to citizenship, various factors such as bureaucratic complexity, limited public understanding of naturalization procedures, and discrimination against minority groups remain significant barriers. Academically, this article contributes to the international discourse on the implementation of non-discrimination principles and the right to citizenship by emphasizing the need to harmonize national law with international legal standards to ensure adequate protection for stateless individuals in Indonesia.